Enablers and inhibitors to the utilization of healthcare services by members of the LGBTQ+ community in Accra, Ghana - Donald Womonia Anuga; Merri Iddrisu; Kennedy Dodam Konlan (Discover Public Health)
Abstract Background Globally, lesbian, gay, bisexual, transgender and queer (LGBTQ+) individuals experience higher rates of mental health disorders, sexually transmitted infections and substance abuse compared to their heterosexual counterparts. This implies that this special population requires tailored healthcare services. However, their practice is criminalized in most countries and abhorred by many, including some health professionals leading to isolation and poor health-seeking behaviors. We explored the enablers and inhibitors to the utilization of healthcare services by members of the LGBTQ+ community in Accra, Ghana. Methods In this cross-sectional study. We collected qualitative data through snowballing sampling technique. Fifteen (15) self-reported persons claiming to be sexually different and being members of the LGBTQ+ community in Accra were recruited for this study. The participants were involved in an in-depth interview using a pre-tested interview guide and the interviews were recorded and transcribed verbatim. We adopted Braun and Clarks’ reflexive thematic analysis approach in analyzing the data with the aid of NVivo 10.0 Results The results identified the facilitators of health seeking as community-friendly health services, affordable and accessible services, and provider-awareness of LGBTQ+ community members’ status. Specifically, privacy, anonymity, confidentiality, inclusivity, positive attitudes, welcoming and supportive environment, and gender-appropriate communication, were identified as community friendly attributes that enhance health-seeking. On the barriers militating access to health care, the following factors were identified: negative provider attitude, financial constraints, and stigmatization among health providers. Participants frequently recounted instances where provider attitudes made them feel dismissed, disrespected, or judged. Instances of discrimination, accusations, poor healthcare largely based on ignorance of unique health needs related to LGBTQ+ and judgmental attitudes of health providers were identified as major barriers to health seeking. Conclusion Positive provider attitudes and LGBTQ+ community-friendly health services promote health-seeking behavior among LGBTQ+ individuals. However, members of the LGBTQ+ community in Ghana are stigmatized by health providers and most health workers are ignorant about the special needs of the LGBTQ+ persons. We recommend that in-service training units of hospitals and health training institutions need to provide comprehensive education to health workers particularly nurses and doctors as well as other professionals on the unique health needs of LGBTQ+ persons as well as inclusive care that addresses the needs of members of the LGBTQ+ community.